2020
DOI: 10.1109/tnsre.2020.3040522
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality Reduction and Motion Clustering During Activities of Daily Living: Three-, Four-, and Seven-Degree-of-Freedom Arm Movements

Abstract: This paper is the first in a two-part series analyzing human arm and hand motion during a wide range of unstructured tasks. The wide variety of motions performed by the human arm during daily tasks makes it desirable to find representative subsets to reduce the dimensionality of these movements for a variety of applications, including the design and control of robotic and prosthetic devices. This paper presents a novel method and the results of an extensive human subjects study to obtain representative arm joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…The prespecified motion trajectories are based on the authors' previous work on arm motions performing activities of daily living (ADL) (Fig. 2) [16]; in total there are 5 trajectories for the 3 DOF device, and 11 trajectories each for the 4 and 7 DOF devices. These trajectories were obtained by clustering and averaging arm motions from healthy participants performing an extensive set of ADL tasks.…”
Section: Trajectory Control -An Effective Strategy For Controlling Mu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The prespecified motion trajectories are based on the authors' previous work on arm motions performing activities of daily living (ADL) (Fig. 2) [16]; in total there are 5 trajectories for the 3 DOF device, and 11 trajectories each for the 4 and 7 DOF devices. These trajectories were obtained by clustering and averaging arm motions from healthy participants performing an extensive set of ADL tasks.…”
Section: Trajectory Control -An Effective Strategy For Controlling Mu...mentioning
confidence: 99%
“…This paper builds upon the authors' previous work, where learned prototypical motions were first developed [16] and tested in a pilot [25], by looking to demonstrate trajectory control as a feasible control method to position and orient the end-effector of various prosthetic devices. A summary of the method that was used to obtain prorotypical motions is included in section II.…”
Section: Trajectory Control -An Effective Strategy For Controlling Mu...mentioning
confidence: 99%
“…The categories and their movement characteristics can provide references for comparing the performance of the artificial limbs with the human limb, thereby encouraging the development of better mechanical or control systems. In practice, motivated by the advantages of the categorization, researchers have built different taxonomies or classification systems for different types of human movements, such as the taxonomies of hand grasps ( Feix et al, 2016 ; Stival et al, 2019 ), whole-body support poses ( Borras et al, 2017 ), and activities of daily living of upper limb ( Gloumakov et al, 2020a ; Gloumakov et al, 2020b ), and the classification systems of normal walking ( Vardaxis et al, 1998 ; Simonsen and Alkjaer, 2012 ), normal running ( Liebl et al, 2014 ; Phinyomark et al, 2015 ), and pathological walking or running ( Kuntze et al, 2018 ; Jauhiainen et al, 2020 ). However, to our knowledge, a quantitative categorization for the various lower limb movements has not been established to date.…”
Section: Introductionmentioning
confidence: 99%
“…For this, references were consulted about the last 5 years from three libraries (IEEExplore, IOPScience and ACM Digital Library). Figure 1 shows the line time of the investigations that have as title "Seven Degrees of Freedom" in the last two years this topic has increase its interest [1][2][3][4][5][6][7][8][9][10]. Within this review of references, 10 articles were found, which were divided into three main topics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the articles describing applications of 7-DOF [1][2][3] were placed in the first topic. The study of the kinematics and dynamics of these manipulators is the most developed topic, proposing templates and methods based on 40% of the Denavit Hartenberg (D-H) algorithm [4][5][6][7][8]. An example is the proposed method for redundant manipulator configuration, obtaining a complete analytical inverse kinematics equation in the position space, which eliminates the Jacobian matrix [6].…”
Section: Introductionmentioning
confidence: 99%